1994
DOI: 10.1029/94ja01977
|View full text |Cite
|
Sign up to set email alerts
|

Ulysses field and plasma observations of magnetic holes in the solar wind and their relation to mirror‐mode structures

Abstract: The term "magnetic hole" has been used to denote isolated intervals when the magnitude of the interplanetary magnetic field drops to a few tenths, or less, of its ambient value for a time that corresponds to a linear dimension of tens to a few hundreds of proton gyro-radii. Data obtained by the Ulysses magnetometer and solar wind analyzer have been combined to study the properties of such magnetic holes in the solar wind between 1 AU and 5.4 AU and to 23 ø south latitude. In order to avoid confusion with decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
277
1
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(299 citation statements)
references
References 29 publications
18
277
1
3
Order By: Relevance
“…To obtain additional examples, we carded out an automated search for magnetic holes. The search algorithm was the same as that described by Winterhalter et al [1994] with the exception that the sliding analysis window was increased from 5 min to 1 hr in order to find longer duration magnetic holes. The search covered the year 1994, when Ulysses was continuously in the high speed wind from the southern polar coronal hole as the spacecraft moved from a solar distance of 3.82 AU and a latitude of 48.4øS, to the southerly most point at 2.29 AU and 80.2øS, to 1.56 AU and 44.6øS.…”
Section: Instrumentation and Methods Of Analysismentioning
confidence: 99%
“…To obtain additional examples, we carded out an automated search for magnetic holes. The search algorithm was the same as that described by Winterhalter et al [1994] with the exception that the sliding analysis window was increased from 5 min to 1 hr in order to find longer duration magnetic holes. The search covered the year 1994, when Ulysses was continuously in the high speed wind from the southern polar coronal hole as the spacecraft moved from a solar distance of 3.82 AU and a latitude of 48.4øS, to the southerly most point at 2.29 AU and 80.2øS, to 1.56 AU and 44.6øS.…”
Section: Instrumentation and Methods Of Analysismentioning
confidence: 99%
“…[8] For the solar wind, magnetic holes have also been observed at various heliocentric distances either as isolated holes or trains of closely-spaced magnetic holes [Winterhalter et al, 1994;Zhang et al, 2008;Russell et al, 2008]. Recently, using STEREO high-resolution magnetic field data, Russell et al [2009] reported several mirror-mode events of small amplitude trains, which included not only holes, but also peaks that persisted for hours and were referred to as "mirror-mode storms".…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in situ observations of mirror-mode waves in thermally anisotropic space plasmas are very frequent [Winterhalter et al, 1994;Liu et al, 2006;Génot et al, 2009]. Space plasma environments where nonuniform heating and compression take place, such as the downstream regions of shocks, are excellent sources for temperature anisotropies in the plasma.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that magnetic field depressions which are bound by directional discontinuities are associated with the excitation of Langmuir waves [Linet al, 1996]. Winterhalter et al [ 1994] studied the occurrence rate and properties of these events in measurements taken by the Ulysses circumsolar spacecraft. They restricted their analysis to length scales below 60 s by using a 300 s sliding window and identified about 2000 events per year with a median duration of 22 s. They further restricted their analysis to holes with a magnetic field rotation of less than 5 ø and a quiet background.…”
Section: Introductionmentioning
confidence: 99%